A case study on the visual and psychological effect of design in selected live music performance on audience impact - Maramag, Athena B.
This study sought to determine whether or not the lighting design and selected live music performances affect audience impact. Using a combination of descriptive and correlational research design, the study focused on the perceptions of selected College students towards the lighting design of live musical performances specifically from three genres namely, Rap, Jazz and Pop, all stage in one venue. Purposeful sampling design was utilized to select 20 respondents, following the criteria wherein they should be College students who witnessed the said live music performances from the 60th Korea-Philippines Friendship Festival held last August 29, 2009. The instrumentation used were survey questionnaires designed to obtain the respondents' perception on the live music performances in terms of lighting design. Copies of personally recorded videos of the said performances in CD format were given out along with the questionnaire to the respondents for recall purposes. A separate interview guide designed for a lighting expert was facilitated. Data gathering occurred within two months. A combination of quantitative and qualitative data analysis procedure was used. Results showed that proper lighting is necessary to the success of live music performances. The respondents found lighting design in live music performances appropriate when conceptualized according to their respective musical style. Rap and Pop were described by the respondents as happy and upbeat music whereas, Jazz was described as mellow and romantic. The respondents' color associations for Rap gave the following: yellow, red, blue and white while Jazz was associated with cool colors such as blue and white. For the Pop performance, red, black, yellow and orange were chosen as its color associations. In terms of overall impact the three musical performances were ranked from highest to lowest with Pop getting the highest impact, Rap in second and Jazz was least.